RISE: Empowering halal research towards sustainability through disruptive technology / Muhamad Afiq Abd Razak - Abd Razak, Muhamad Afiq (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Since the introduction of the Malaysian Halal Certification Scheme, research on halal has emerged and expanded ever since. Halal now has become a full-fledge body of knowledge of its own discipline and subdisciplines. Although the basis of halal research stems on the syariah principles, but today it has been broadened to various fields which includes halal industry management, halal science, halal consumerism, naming a few. With the establishment of new schemes offered by JAKIM -Malaysian Halal Certification Scheme, halal research developed multi-faceted areas that includes halal food, halal pharmaceuticals, halal cosmetics, halal logistics, halal consumer goods, halal food services, halal tourism, and halal medical device. Therefore, halal research can be regarded as reaching to its maturity and apex, and has become a strategic move into spearheading halal industry.